H2 Dysphagia in huntington's disease (HD): a longitudinal, observational study. (13th September 2016) - Schradt, Falk; Geitner, Carolin; Lindner-Pfleghar, Beate; Rea, Daniela; Hamilton, Alison; Lang, Christina; Süssmuth, Sigurd D; Weydt, Patrick; Schumann, Beate; Werner, Cornelius
Abstract : Background: Dysphagia is a common problem in HD. 1, 2, 3 Swallowing function becomes increasingly impaired, increasing the risk of aspiration and pneumonia, the most common cause of mortality. 3 An evidence-based rationale for the development and evaluation of timely and complex SLT interventions is required to confirm that swallow training is beneficial in HD and at what disease stages interventions are most likely to be beneficial. This also helps to choose reliable and feasible outcome-measures, including instrumental assessments visualising the structure and function of different stages of swallow. Aims: collect longitudinal data to assess the features of the dysphagia in HD identify possible risk factors for severity of the dysphagia and aspiration evaluate a range of dysphagia related outcome measures Methods: We investigated 61 patients retrospectively and 25 patients prospectively to describe features of the swallowing disorder (such as residues, leaking, penetration/aspiration) dependent on consistencies and their correlation with the motor stage of HD. For clinical swallowing examination we used the NOD-Stepwise Concept. 4 Instrumental assessment to visualise the structure and functions of the different stages of swallowing and to identify the risk of aspiration was Fiberoptic Endoscopic Evaluation of Swallowing (FEES). The examination was complemented by the Swallowing Quality of life survey (SWAL-QOL). 5 Results: Subclinical Dysphagia was found in HD patients at all stages of the disease. Clinical predictors like dysarthria and dysphonia for the risk of aspiration as well as effective compensatory strategies were identified. References: Heemskerk AW, Roos RAC, ASHA Perspectives on Swallowing and Swallowing disorders, Review 2012;21 (4):126–134 Hamilton, et al. Oral feeding in Huntington's Disease: a guideline document for speech and language therapists. Neurodegen. Dis Manage 2012;2 (1):45–53 Heemskerk AW, Roos RAC. Aspiration Pneumonia and death in Huntington's Disease. PLoS currents HD 2012 Ickenstein GW, Hofmayer A, Lindner-Pfleghar B, Pluschinski B, Riecker A, Schelling A, Prosiegel M. Standardisierung des Schluckablaufs bei neurogener oropharyngealer Dysphagie. Neurologie und Rehabilitation (2009) McHorney CA, Robbins J, Lomax K, Rosenbek JC, Chignell K, Kramer AE, Bricker DE. The SWAL-QOL and SWAL-CARE outcomes tool for oropharyngeal dysphagia in adults: III. Documentation of reliability and validity. Dysphagia 2002;17 (2):97–114